The anatomy of an assassination: Assassination of Mahmud Şevket Paşa (11 June 1913) - Gündoğdu, Cihangir. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2004., 2004)
Mahmut Şevket Paşa was one of the most significant military and political figures of the Second Constitutional Period. Coming to İstanbul as the commander of the Action Army in the time of 31 March Uprising, he turned to become a defining feature of almost all military and political developments. As well as his reforms and policies in his life time, he managed to leave apparent traces in the Ottoman Empire together with his death thus making shifts in the balance of political power. The objective of this study is to revisit the assassination of Mahmud Şevket Paşa who played an effective role in the Second Constitutional Period and to seek to understand political and social drives, the assassinators' personal motivations, the developments in the assassination and implications of the assassination in the light of present papers, periodicals, archival documents and memoirs.